(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Psychosocial experiences such as life-orientation, subjective well-being and social support are punitive in determining the health related quality of life of patients in end stage of Chronic Renal Disease; also termed as End Stage Renal Disease (ESRD). Objectives: to investigate the phenomenon of life-orientation, subjective well-being, social support and perceived health related quality of life in patients with end stage renal disease. ESRD patients life orientation, social support and subjective well-being are significant predictors of their perceived quality of life that further determines their disease management and health status. Materials and Methods: This research has been laid out through cross sectional survey research design. The data was collected between the time span of Jan, 2016 to June, 2016. The sample comprised of 200 respondents from both gender, equally distributed within the age range of 50 to 60 years, going through last stage of ESRD and relying on dialysis from at least past one year or more. Indigenously translated WHO QoL, Subjective Wellbeing Scale, multidimensional Social Support Scale, Life Orientation Scale and a demographic information sheet was used to collect the data. Results: The results revealed that life orientation, social support and subjective well-being significantly and positively predicted the health related quality of life; greater social support and higher levels of subjective wellbeing after controlling for the effects of age, gender, income and education were found when the patients carried optimistic and positive life-orientation. Conclusion: The current research findings therefore incriminate preemptive direction in understanding the phenomenon of life-orientation, social support, subjective wellbeing and health related quality of life in patients with last stage ESRD. This further embarks onto highlighting the insightful guidelines for health and clinical psychologists in devising management interventions, targeting the increased subjective well-being, and promotion of optimistic life-orientation in order to facilitate health related quality of life in the patients with end stage renal disease. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.346-353